Efficient synthetic methodology for the construction of dihydronaphthalene and benzosuberene molecular frameworks. Issue 5 (31st January 2019) - Mondal, Deboprosad; Niu, Haichan; Pinney, Kevin G.
Graphical abstract: Highlights: Efficient synthetic methodology for benzosuberene and dihydronaphthalene analogues. Methodology accommodated larger scale reactions. Palladium catalyzed amination converted phenolic analogues to aniline congeners. Abstract: Benzosuberene analogues (1 and2 ) and dihydronaphthalene analogues (3 and4 ) function as potent inhibitors of tubulin polymerization, demonstrate pronounced cytotoxicity (low nM to pM range) against human cancer cell lines, and are promising vascular disrupting agents (VDAs). As such, these compounds represent lead anticancer agents with potential translatability towards the clinic. Methodology previously established by us (and others) facilitated synthetic access to a variety of structural and functional group modifications necessary to explore structure activity relationship considerations directed towards the development of these (and related) molecules as potential therapeutic agents. During the course of these studies it became apparent that the availability of synthetic methodology to facilitate direct conversion of the phenolic-based compounds to their corresponding aniline congeners would be beneficial. Accordingly, modified synthetic routes toward these target phenols (benzosuberene1 and dihydronaphthalene3 ) were developed in order to improve scalability and overall yield [45-57% (1 ) and 32% (3 )]. Moreover, benzosuberene-based phenolic analogue1 and separately dihydronaphthalene-based phenolic analogue3 were successfully converted into their corresponding aniline analogues2 and4 in good yield (>60% over three steps) using a palladium catalyzed amination reaction.